Upland processes and controls on September 2013 debris flows, Rocky Mountain National Park, Colorado - Patton, Annette, author; Rathburn, Sara, advisor; Wohl, Ellen, committee member; Niemann, Jeffrey, committee member; Bilderback, Eric, committee member (Colorado State University. Libraries, 2016)
More than 10 large debris flows occurred in and near Rocky Mountain National Park (RMNP) following the spatially extensive September 2013 rainstorm in the Colorado Front Range. These debris flows delivered sediment to valley bottoms and had the potential to damage infrastructure and endanger park visitors and staff. To characterize conditions of debris flow initiation when known thresholds of elevation, slope angle, and rainfall intensity are met, 11 debris flow sites in RMNP were surveyed. Slope variables including soil depth, soil texture, and slope morphology were compared between 11 failed and 30 undisturbed hillslopes (control sites) that were exposed to similar cumulative rainfall during the 2013 storm. Analysis of measured slope variables indicates that slope morphology is strongly related to debris flow occurrence. Four of the 11 surveyed debris flows initiated in or immediately below a colluvial hollow (a topographic concavity on a hillslope), while only 1/30 control sites were located near a colluvial hollow. Furthermore, 8/11 surveyed debris flows initiated in areas of convergent topography (including colluvial hollows and areas of broader convergence), while only 3/30 control slopes were convergent. The differences in these proportions suggest that hillslopes characterized by a colluvial hollow or other convergent topography accumulate surface and groundwater flow and collect unconsolidated material. Convergent hillslopes are therefore more susceptible to slope failure during rain events of sufficient intensity and/or duration. The other geomorphic hillslope variables evaluated in this study did not demonstrate statistically significant differences between debris flow sites and control sites. In some cases, small sample size or other data constraints may provide limited ability to discern geomorphic differences between debris flows and control sites. The Bighorn site, a large debris flow near an historic structure in RMNP, was selected for detailed geochronologic study to determine the ages of old debris deposits and evaluate debris flow frequency. Several numeric and relative dating techniques were applied to determine the age of pre-2013 debris deposits at this site. Numeric dating techniques included radiocarbon analysis of organic material and 10Be radionuclide analysis of boulders collected from four debris flow levees. 10Be exposure dating has not previously been applied to debris flow surfaces. Mapping of debris flow levees and stratigraphic study at the Bighorn debris flow site confirm that at least 2-3 and possibly more debris flows have occurred at this site within the last 102-103 years. The recurrence of debris flows at this site indicates that it may experience similar mass movements in the future. A boulder sample collected from the 2013 debris flow levee returned an 18.1 ka 10Be exposure age. Ranges of exposure ages for three older debris deposits are 54.2, 143, and 121 ka. The falsely old age of the 2013 sample and the wide range of ages determined for each of the older landforms indicate that exposure histories of debris deposits are complicated by inherited atmospheric exposure prior to debris flows. Radiocarbon ages of material collected from this site are on the order of 100-102 years old and do not cluster according to the landform sampled. The results of this study demonstrate that debris flow initiation is governed by a complex interaction of geomorphic and climate variables across a range of spatial and temporal scales. Additionally, the scatter of ages established for old debris flow deposits at the Bighorn debris flow site suggests that debris deposits continue to be modified by secondary processes after the initial event. The downslope pathway of debris flow material reflects highly individual histories from source to sink to deposition near the valley bottom. The numerous debris flows that initiated in the 2013 storm exemplify ongoing debris flow hazards in the Colorado Front Range and highlight the need for awareness of hillslope hazards in this region.